Exploring the gene regulation response of , pathogenic Escherichia coli ATCC BAA-196 and Staphylococcus aureus ATCC BAA-39 exposed to synthesized iodine containing complexes used as potential antimicrobials - Reva, Oleg N. (University of Pretoria, 2022)
Dissertation (MSc (Bioinformatics))--University of Pretoria, 2022.